PENGGUNAAN MODEL PEMBELAJARAN BERPIKIR, BERPASANGAN DAN BERBAGI (THINK PAIR SHARE) OLEH GURU MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH AL-MUSLIMUN TIGARUN KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA: PENGGUNAAN MODEL PEMBELAJARAN THINK PAIR SHARE PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH - Ria Susanti (IAI DARUL ULUM KANDANGAN, 2025)
This research aims to determine how the use of the think pair share learning model by the subject teacher of Akidah Akhlak at MI Al-Muslimun Tigarun, Amuntai Tengah District, Hulu Sungai Utara Regency. The type of research used is field research, while the research approach used is a qualitative research approach. The subjects of this study were grade VI students at MI Al-Muslimun Tigarun. While the object of this study is the use of the think pair share learning model by the subject teacher of Akidah Akhlak at MI Al-Muslimun Tigarun, Amuntai Tengah District, Hulu Sungai Utara Regency. The results of the study showed that the think pair share learning method in learning Akidah Akhlak at MI Al-Muslimun Tigarun was implemented systematically and effectively. Teachers play an active role as facilitators and mentors, while students show a positive response because this method helps shape social character. Despite the challenges, the implementation of this method has a positive impact on the learning process.